Water Quality Assessment using Selected Macroinvertebrate Based Indices and Water Quality Index of Sungai Air Hitam Selangor - Abu Sama, Harisham; Yuzir, Muhammad Ali; Azman, Shamila (Tecno Scientifica Publishing, 2024)
A study was conducted from July to December 2022 at Sungai Air Hitam, a small tributary of the Selangor River located within the Tanjung Karang Sub-basin in Malaysia (coordinates: 3° 24' 27